Fostering Intercultural Understanding: A Reading-Based Framework for Islamic Universities in the International Context - Rahman, Muthia; Abdul Manaf, Azimah; Lismay, Leli (GIC Proceeding, 2024)
The requirement for promoting intercultural understanding has slowly increased today’s globalized world, particularly in the so-called broader society of higher education. In this article, an overarching framework is proposed for the development of intercultural competence among students in Islamic Universities engaged in all domains situated at the global level. Based at the intersection of language education, cultural studies, and international relations, the framework articulates a reading-based approach that promotes students’ exposure to diverse perspectives from other international contexts as well sharing knowledge in a dialog issue. By bringing together theoretical insights, pedagogical strategies and practical suggestions: this framework seeks to provide a systematic and flexible guide for Islamic universities in the inclusion of intercultural deprives